(untitled) (TAJ: Journal of Teachers Association, 2009)
In a prospective, randomized study, 80 patients with lower urinary tract symptoms (LUTS) caused by small prostate gland (estimated weight <30gm) had either transurethral resection (TURP, n=40) or transurethral incision (TUIP, n=40) of prostate. The study was conducted in the Department of Urology, BSMMU, Dhaka and Rajshahi Medical College Hospital, Rajshahi. Aims of the study were to evaluate the efficacy of TUIP as a treatment modality for small size obstructive BPH and to compare its outcome with that of TURP. A relative advantage of TUIP over conventional TURP was also observed in this study. Preoperative variables (symptom scores, PVR, uroflowmetry parameters) were well matched in between TURP and TUIP group. TURPs were done in conventional technique. For TUIP, two deep incisions were made at 5- and 7-0’clock positions of the bladder neck using Colling’s knife. Operative variables (operating time, amount of irrigation fluid and blood transfusion required) were observed and recorded. Postoperative catheterization period and hospital stay (in days) were noted. All patients were followed up at 3 to 4 months postoperatively. Changes of preoperative variables following surgery were assessed. Sexual functions were also questioned and noted pre- and postoperatively. The study clearly indicated that TUIP is as effective as TURP for the treatment of small sized obstructive BPH. Alterations of sexual functions are similar in both the procedures. On the other hand, operating time, requirement of irrigation fluid and blood transfusion, postoperative catheterization period and hospital stay are significantly (P>0.001) less in TUIP group than that of TURP. In conclusion, we recommend TUIP for the treatment of LUTS caused by small size obstructing benign prostatic hyperplasia. doi: 10.3329/taj.v19i2.3149 TAJ 2006; 19(2): 50-56